2008
DOI: 10.1111/j.1365-2982.2008.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor 2 and gut permeability: a review

Abstract: Digestive tract proteases are best known for their proteolytic activity in the digestion of alimentary proteins. However, during the last decade, a possible role of proteases as signalling molecules has been emphasized with the discovery of a novel class of G-protein coupled receptors located on cell membranes that may be activated by proteolytic cleavage of their N-terminal extracellular domain. Type 2 protease-activated receptors (PAR-2) are cleaved by serine-proteases such as trypsin and tryptase. PAR-2 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 48 publications
2
45
0
1
Order By: Relevance
“…The role of both EGFR and PAR 2 in regulating epithelial permeability has been previously reported (33,34). However, our study provides previously undescribed evidence that the 2 receptors work cooperatively to regulate small intestine permeability.…”
Section: Discussionsupporting
confidence: 53%
“…The role of both EGFR and PAR 2 in regulating epithelial permeability has been previously reported (33,34). However, our study provides previously undescribed evidence that the 2 receptors work cooperatively to regulate small intestine permeability.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, epithelial barrier dysfunction contributes to fibrosis 38 -40 and PAR-2 activation seems to increase epithelial permeability in different organs. [41][42][43] In the lung, PAR-2 activation causes a rapid and transient increase in permeability of airway epithelium that persists for 6 to 10 minutes. Our results support and extend these observations by showing that longer stimulation results in a persistent PAR-2Ϫdependent increase in epithelial permeability (Supplemental Figure S3, http://ajp.amjpathol.org/).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others have shown that the disruption of epithelial barrier in IBD and IBS is attributed to destruction of ZO-1 and Occludin-1 TJs 1 2 14–18. The mechanisms proposed include elevated luminal cysteine19 and serine20 protease activity resulting in direct TJ protein destruction and/or indirect activation of PAR-2 14 21 22. Using experimental models of colitis, PAR-2 antagonist have been shown to be effective in ameliorating IBD-like pathology and symptoms;18 21 22 however their effect remains to be tested in humans.…”
Section: Introductionmentioning
confidence: 99%